Analysis Of Metallize Product Quality Control Using The Plan Do Check Action (PDCA) Methods at PT. Polyplex Films Indonesia - Sartono Sartono; Dedy Khaerudin; Mislan Mislan; Ganjar Sidik Gandara; Irma Nurmala Dewi (Proceeding of the International Conference on Electrical Engineering and Informatics, 2024)
PT. Polyplex Films Indonesia is a manufacturer of Metallize Film products. This polymer film is coated with a tiny aluminum foil coating, giving it a bright metallic appearance. Metalized film materials have extensive use in decoration, food packaging, and specialized uses, including insulation and electronics. The production results of metalized film production show that in the most recent year, 2022, the number of defects was 1.6%, which is higher than the tolerance limit the company set at 0.5% of total annual production. Maintaining the consistency of the quality of the metalized film products that the company produces is much easier. The number of defects settled by the different types: Heat line accounts for 42% of the defects, pinhole accounts for 31%, and Star sky accounts for 27%. The company employs the PDCA method to mitigate issues in the production line. The implementation results demonstrate that the PDCA method has led to a reduction in the number of defects. Specifically, the Heat Line defects decreased from 274 tons to 57 tons, representing a decrease of 79.19%. Similarly, the Star Sky defects decreased from 178 tons to 85 tons, resulting in a reduction of 52%. The pinhole defects decreased from 202 to 51 tons, indicating a 74.8% decrease. The findings of this study should deepen our understanding of how the PDCA technique actually works to enhance product quality. This is because the changes are produced during the action phase, allowing for long-term retention of the gains. Product recommendations for additional investigation include PET (polyethylene terephthalate), BOPP (bi-axially oriented polypropylene), and CPP (cast polypropylene) films.